The MAS and After: Transubstantiating Theory and Practice into an Archival Culture - Klumpenhouwer, Richard (Archivaria, 1995)
Does the Master of Archival Studies Programme (MAS) produce archival graduates who are all theory and no practice? To deal with this charge, the author explores his own history as an MAS graduate and archival practitioner. He contends that the MAS experience transcended merely acquiring theoretical or practical knowledge and that, therefore, the dichotomy does not really apply. The whole process served as a kind of initiation into an archival culture. The graduate student's theorizing and practicing go beyond learning ideas, facts, or methods; they are rituals and ordeals on the road to archival adulthood. The development of this identify with the theories, practices, and personalities of archival culture sustains graduates as they live out their careers in the larger world. RÉSUMÉ Une Maitrise en études archivistiques produit-elle des théoriciens sans connaissances pratiques? Pour répondre àcette question, l'auteur explore sa propre démarche de diplômé en études archivistiques et son expérience d'archiviste. I1 soutient que son expérience transcende l'acquisition d'un savoir théorique ou pratique. Pareille dichotomie n'existe pas. L'ensemble du processus s'avère plutôt une initiation àla culture archivistique. L'effort théorique et l'exercice de la pratique outrepassent les idées reçues, les faits, ou les méthodes; elles constituent davantage des rituels et des épreuves initiatiques sur la route de la maturité archivistique. Le développement de cette identité, conjointement avec les théories, les pratiques, et les grands noms de la culture archivistique soutiennent les diplômés durant leurs carrières professionnelles.